Clinical characteristics and factors associated with severe acute respiratory infection and influenza among children in Jingzhou, China. Issue 2 (20th September 2016) - Huai, Yang; Guan, Xuhua; Liu, Shali; Uyeki, Timothy M.; Jiang, Hui; Klena, John; Huang, Jigui; Chen, Maoyi; Peng, Youxing; Yang, Hui; Luo, Jun; Zheng, Jiandong; et al.
Abstract : Background: Influenza is an important cause of respiratory illness in children, but data are limited on hospitalized children with laboratory‐confirmed influenza in China. Methods: We conducted active surveillance for severe acute respiratory infection (SARI; fever and at least one sign or symptom of acute respiratory illness) among hospitalized pediatric patients in Jingzhou, Hubei Province, from April 2010 to April 2012. Data were collected from enrolled SARI patients on demographics, underlying health conditions, clinical course of illness, and outcomes. Nasal swabs were collected and tested for influenza viruses by reverse transcription polymerase chain reaction. We described the clinical and epidemiological characteristics of children with influenza and analyzed the association between potential risk factors and SARI patients with influenza. Results: During the study period, 15 354 children aged <15 years with signs and symptoms of SARI were enrolled at hospital admission. severe acute respiratory infection patients aged 5–15 years with confirmed influenza (H3N2) infection were more likely than children without influenza to have radiographic diagnosis of pneumonia (11/31, 36% vs 15/105, 14%. P <.05). Only 16% (1116/7145) of enrolled patients had received seasonal trivalent influenza vaccination within 12 months of hospital admission. Non‐vaccinated influenza cases were more likely than vaccinated influenza cases to have pneumonia (31/133, 23% vs 37/256, 15%, P <.05). severe acute respiratory infection cases aged 5–15 years diagnosed with influenza were also more likely to have a household member who smoked cigarettes compared with SARI cases without a smoking household member (54/208, 26% vs 158/960, 16%, P <.05). Conclusions: Influenza A (H3N2) virus infection was an important contributor to pneumonia requiring hospitalization. Our results highlight the importance of surveillance in identifying factors for influenza hospitalization, monitoring adherence to influenza prevention and treatment strategies, and evaluating the disease burden among hospitalized pediatric SARI patients. Influenza vaccination promotion should target children.